CRISPRi-mediated functional analysis of NKX2-1-binding sites in the lung - William D. Stuart (Nature Portfolio, 2021)
The transcription factor NKX2-1 is a key regulator of lung pathophysiology, but the importance of its binding sites outside of proximal promoter regions is unclear. Here, William Stuart and Iris Fink-Baldauf et al. use CRISPRi to interrogate 19 NKX2-1 binding sites and identify specific sites important for breathing, innate immune defense, and tumorigenesis.